# If $\sin \left( {90 - \theta } \right) + \cos \theta = \sqrt 2 \cos \left( {90 - \theta } \right),$for $0 < \theta < {90^0}, $find the value of $\cos ec\theta $.

$

{\text{A}}{\text{. }}\frac{{\sqrt 3 }}{2} \\

{\text{B}}{\text{. }}\frac{2}{{\sqrt 3 }} \\

{\text{C}}{\text{. }}\sqrt {\frac{3}{2}} \\

{\text{D}}{\text{. }}\sqrt {\frac{2}{3}} \\

$

Answer

Verified

361.2k+ views

Hint: - For solving this type of question you have just knowledge of trigonometric transformation and just simple mathematics to proceed further. You have to transform as you can shorten the complex equation in easy form.

As given in question

$\sin \left( {90 - \theta } \right) + \cos \theta = \sqrt 2 \cos \left( {90 - \theta } \right)$

We know $\left( {\because \sin \left( {90 - \theta } \right) = \cos \theta } \right)\left( {\because \cos \left( {90 - \theta } \right) = \sin \theta } \right)$

$ \Rightarrow \cos \theta + \cos \theta = \sqrt 2 \sin \theta $

$ \Rightarrow 2\cos \theta = \sqrt 2 \sin \theta $$ \Rightarrow \frac{{\cos \theta }}{{\sin \theta }} = \frac{{\sqrt 2 }}{2} = \frac{1}{{\sqrt 2 }}$

We know $\left( {\frac{{\cos \theta }}{{\sin \theta }} = \cot \theta } \right)$

$ \Rightarrow \cot \theta = \frac{1}{{\sqrt 2 }}$ $\left( {\because \cos e{c^2}\theta - {{\cot }^2}\theta = 1} \right)\left( {\therefore \cot \theta = \sqrt {\cos e{c^2}\theta - 1} } \right)$

$ \Rightarrow \sqrt {\cos e{c^2}\theta - 1} = \frac{1}{{\sqrt 2 }}$

Squaring on both side, we get

$ \Rightarrow \cos e{c^2}\theta - 1 = \frac{1}{2}$

$\therefore \cos e{c^2}\theta = \frac{3}{2} \Rightarrow \cos ec\theta = \sqrt {\frac{3}{2}} $

Hence the option ${\text{C}}$is the correct option.

Note: -Whenever you get these types of questions the key concept of solving is you have to proceed from the question and just use trigonometric results to get an answer. You have to shorten the complex equation using standard results.

__Complete step-by-step solution -__As given in question

$\sin \left( {90 - \theta } \right) + \cos \theta = \sqrt 2 \cos \left( {90 - \theta } \right)$

We know $\left( {\because \sin \left( {90 - \theta } \right) = \cos \theta } \right)\left( {\because \cos \left( {90 - \theta } \right) = \sin \theta } \right)$

$ \Rightarrow \cos \theta + \cos \theta = \sqrt 2 \sin \theta $

$ \Rightarrow 2\cos \theta = \sqrt 2 \sin \theta $$ \Rightarrow \frac{{\cos \theta }}{{\sin \theta }} = \frac{{\sqrt 2 }}{2} = \frac{1}{{\sqrt 2 }}$

We know $\left( {\frac{{\cos \theta }}{{\sin \theta }} = \cot \theta } \right)$

$ \Rightarrow \cot \theta = \frac{1}{{\sqrt 2 }}$ $\left( {\because \cos e{c^2}\theta - {{\cot }^2}\theta = 1} \right)\left( {\therefore \cot \theta = \sqrt {\cos e{c^2}\theta - 1} } \right)$

$ \Rightarrow \sqrt {\cos e{c^2}\theta - 1} = \frac{1}{{\sqrt 2 }}$

Squaring on both side, we get

$ \Rightarrow \cos e{c^2}\theta - 1 = \frac{1}{2}$

$\therefore \cos e{c^2}\theta = \frac{3}{2} \Rightarrow \cos ec\theta = \sqrt {\frac{3}{2}} $

Hence the option ${\text{C}}$is the correct option.

Note: -Whenever you get these types of questions the key concept of solving is you have to proceed from the question and just use trigonometric results to get an answer. You have to shorten the complex equation using standard results.

Last updated date: 21st Sep 2023

â€¢

Total views: 361.2k

â€¢

Views today: 5.61k